2018
DOI: 10.1002/pon.4829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of existential interventions on spiritual, psychological, and physical well‐being in adult patients with cancer: Systematic review and meta‐analysis of randomized controlled trials

Abstract: This systematic review and meta-analysis provides evidence that adult patients with cancer across all stages and types benefit from existential interventions. Future research should strive towards a higher standardization in particular with respect to outcome assessments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(75 citation statements)
references
References 78 publications
2
68
0
5
Order By: Relevance
“…Our results suggest that psychosocial interventions can increase a sense of meaning and purpose in patients with cancer and survivors, especially if they are explicitly designed to do so and focus on enhancing patients' sense of meaning and purpose. 26,92 These interventions are generating growing interest, [18][19][20][21][23][24][25] and thus, we anticipate that development and testing of meaningrelated interventions will increase fairly rapidly. Because meaning and purpose have been conceptualized in different ways and encompass multiple distinct dimensions, 4 it will be important for future studies to consider carefully and delineate more clearly what aspects of meaning the intervention is intended to target and to differentiate these endpoints from related concepts (such as spirituality or general well-being).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results suggest that psychosocial interventions can increase a sense of meaning and purpose in patients with cancer and survivors, especially if they are explicitly designed to do so and focus on enhancing patients' sense of meaning and purpose. 26,92 These interventions are generating growing interest, [18][19][20][21][23][24][25] and thus, we anticipate that development and testing of meaningrelated interventions will increase fairly rapidly. Because meaning and purpose have been conceptualized in different ways and encompass multiple distinct dimensions, 4 it will be important for future studies to consider carefully and delineate more clearly what aspects of meaning the intervention is intended to target and to differentiate these endpoints from related concepts (such as spirituality or general well-being).…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] A recent wave of interventions for patients with cancer has been specifically designed to address existential/ spiritual concerns or questions of personal meaning. [18][19][20][21][22][23][24][25][26] Psychosocial interventions designed to influence a wide array of psychological and even physical health outcomes might also affect meaning-related endpoints, even if these are not their singular or primary emphasis (eg, coping skills, health education, or creative arts programs). A large and growing research base has evaluated psychosocial interventions for patients with various malignancies, and many of these trials have included outcomes concerning meaning or purpose.…”
Section: Introductionmentioning
confidence: 99%
“…The two meta‐analyses featured in this issue reflect substantial progress since the review by LeMay and Wilson . Bauereiss et al have identified 30 RCTs testing existential therapies in predominantly advanced cancer patients, including trials of Supportive‐Expressive Group Therapy, Cognitive‐Existential Group Therapy, Dignity Therapy, Meaning‐Centered Psychotherapy, Managing Cancer and Living Meaningfully (CALM) Therapy, and the Life Review, Narrative, Hope, and Meaning‐Making Intervention. While significant small to moderate pooled effects on post‐treatment quality of life and existential well‐being have emerged for existential therapies over control conditions, effects on anxiety and depression were significant only after exclusion of four studies with baseline group differences suggesting randomization difficulties.…”
Section: How Do We Ameliorate Existential Distress?mentioning
confidence: 99%
“…Although existential suffering in the context of life‐threatening illness has long been called to attention, only recently have researchers studied this phenomenon more rigorously. Common to this proliferating body of literature is the conceptualization of existential distress as a distinct, painful psychological state that results from a stressor that challenges fundamental expectations about security, interrelatedness with others, justness, controllability, certainty, and hope for a long and fruitful life; brings a flood of distressing emotions including fear, outrage and horror at the possibility of death; concern about autonomy, suffering, or being a burden to others; a sense of profound loneliness, pointlessness, or hopelessness; grief, regret, or embitterment about what has been missed in life; and shame if dignity is lost, doubt and disbelief prevail, or expectations about coping are not met; has been operationalized by the constructs of fear of cancer recurrence , death anxiety , demoralization , dignity‐related distress , hopelessness , spiritual distress , and the desire for hastened death , which include the aforementioned facets in varying combination and emphasis; fluctuates and occurs on a continuum of severity, where severe and enduring levels are clinically significant and maladaptive in a noteworthy subgroup; may occur comorbidly with other psychiatric disorders but also in their absence, when physical pain is well treated, social support is available, and the person has been perceived as robust; and finally has a significant impact on health care outcomes. Two meta‐analyses featured in this issue illustrate the progress of the last decade. Yet there is much uncertainty about how to recognize and address existential distress in cancer care.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a growing body of literature on existential and dignity-related distress. Bauereiss, Obermaier, Ozunal, and Baumeister (2018) synthesized the evidence of existential interventions in adult patients with cancer. Robinson, Kissane, Brooker, and Burney (2015) synthesized the recent empirical evidence on demoralization in patients with progressive disease or cancer.…”
Section: Introductionmentioning
confidence: 99%